Relationship Adolescent perceptions about the maturity of the reproductive organs with sexual behavior deviations - Riana Safitri; Mudjiran Mudjiran; Z Mawardi Effendi (International Journal of Applied Counseling and Social Sciences, 2019)
The deviations of sexual behavior are the behavior or behaviour that is not necessarily done by each individual in the course of teenagers as humans who are experiencing the transition or transitioning as not in accordance with the norms Applicable, whether it is religious norms, customs and legal norms. Nowadays, there have been many sexual behavior deviations done by the teenagers such as holding hands with the opposite sex, embracing, kissing, and even having intercourse like a husband and wife. Sexual behavior deviations are caused by internal and external factors. Internal factors can occur due to the sexual arousal that occurs in the age of adolescence and want to channel it to the opposite sex, while external factors can occur due to the environment that makes adolescents commit sexual behavior irregularities, as there are pornographic sites seen by teenagers, then they demonstrate with the opposite sex and lack the education. The purpose of this research is to look at the adolescent perception relationship about the maturity of reproductive tools with sexual behavior deviations. This study uses propotional stratiefied random sampling techniques. Based on research done, it was found that there was a significant link between juvenile perception of the maturity of reproductive tools and sexual behavior deviations.